MANAGEMENT OF MARKET LAUNCHING OF A NEW PRODUCT (ON THE EXAMPLE OF THE COSMETIC PRODUCTS MARKET) - NIESHEVA, Anastasiia; VASYLIEVA, Tetiana; KUTSENKO, Vladyslav; NEBABA, Natalia (Herald of Khmelnytskyi National University. Economic sciences, 2023)
Management of introducing new products to the cosmetics market is a crucial task in today’s competitive business environment, driven by evolving consumer expectations. This article aims to explore key aspects of this process and identify prospects for further research in this domain. First and foremost, understanding consumer needs is paramount. In the cosmetics market, it is essential to grasp which products and features appeal to consumers. Consumer trends evolve, and researching these changes is instrumental in developing products that meet current demands. Secondly, innovation in product development is essential. Utilizing cutting-edge technologies and ingredients in the creation of new cosmetic products can provide a competitive edge. It is imperative to investigate and implement novel technologies that enhance product quality and effectiveness. Effective marketing planning and branding are pivotal factors in successfully launching cosmetic products. Scientific approaches assist in crafting marketing strategies that capture consumers’ attention and establish enduring brand identities. Compliance with standards and regulations is also of paramount importance for practical product launch. Adhering to legislative requirements and standards regarding the safety and quality of cosmetic products is obligatory to gain consumer trust. Furthermore, studying the competitive landscape and formulating effective market entry strategies are essential practical tasks for businesses in the cosmetics industry. Only through deliberate research and strategic planning can success be achieved in this highly competitive field. In conclusion, this article aims to investigate and analyze various aspects of managing the introduction of new cosmetic products to the market and identify prospects for further research in this sphere, ultimately contributing to the enhancement of product quality and competitiveness in this vital market.